Artifacts in 3D Prenatal Sonography - Miric Tesanic, Danka; Merz, Eberhard (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Artifacts may be part of any 3D sonographic examination during pregnancy and can disturb a routine diagnostic procedure, even simulate fetal malformation. The aim of this study was to classify the artifacts in different types according to their appearance.Materials and Methods A total of 2349 healthy fetuses examined during the last five years was included in this study. The observed artifacts have been grouped into 6 different types according to their appearance: 1. fetal movement artifacts, 2. shadow artifacts, 3. amputation artifacts caused by the volume box, 4. defects caused by the improper use of the electronic scalpel, 5. artifacts due to an unfavorable threshold adjustment and 6. artifacts due to superimposed objects.Results Significant artifacts were found in 119 ultrasound examinations: 39 artifacts were caused by fetal movement, 25 by acoustic shadowing, 19 artifacts occurred due to amputation of objects by the volume box and 15 by the improper use of the electronic scalpel. In 12 cases the threshold adjustment was unfavorable and in 9 cases the artifacts were caused by superimposed objects.Conclusion In 3D ultrasound some artifacts can be avoided by optimizing the size and position of the volume box or by using a different scanning angle. Other artifacts can be minimized using gain and threshold properly and by precise use of the electronic scalpel. In doubtful situations it is recommended to rescan the volume and to use all diagnostic 3D rendering possibilities. Proper recognition of the artifacts can avoid the risk of misdiagnosis.
Keywords: 3D ultrasound; prenatal sonography; sonographic artifacts